2009
DOI: 10.1007/s10826-009-9278-6
|View full text |Cite
|
Sign up to set email alerts
|

Conduct Disordered Youth in Group Care: An Examination of Negative Peer Influence

Abstract: We examined the potential impact of negative peer influence within a treatment-focused residential care setting. Subjects were 712 youth consecutively admitted to a large residential treatment program (9-19 years of age). Based on Diagnostic Interview Schedule for Children (DISC) scores, 247 (35%) of these youth qualified for a Conduct Disorder diagnosis at admission. The dependent measures were the number of DISC Oppositional Defiant Disorder (ODD)/Conduct Disorder (CD) symptoms and the sum of Conduct Problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Dishion et al (1999) suggested in their seminal review that aggregating antisocial youth, particularly adolescents, in group treatments might produce the iatrogenic effect of increasing problem behaviors in those youth. Although not all studies of deviant peer influence have yielded negative peer contagion effects (some have shown both positive and negative influence or generally positive influence of deviant peers; Boxer, Guerra, Huesmann, & Morales, 2005;Huefner, Handwerk, Ringle, & Field, 2009), negative peers certainly appear to play a meaningful role in whether individual youth can make changes for the better in their positive adjustment.…”
mentioning
confidence: 99%
“…Dishion et al (1999) suggested in their seminal review that aggregating antisocial youth, particularly adolescents, in group treatments might produce the iatrogenic effect of increasing problem behaviors in those youth. Although not all studies of deviant peer influence have yielded negative peer contagion effects (some have shown both positive and negative influence or generally positive influence of deviant peers; Boxer, Guerra, Huesmann, & Morales, 2005;Huefner, Handwerk, Ringle, & Field, 2009), negative peers certainly appear to play a meaningful role in whether individual youth can make changes for the better in their positive adjustment.…”
mentioning
confidence: 99%
“…Thus, it is possible that the MIP classrooms provided a negative counterbalance to the positive effects of MST, reducing its effects. Actual evidence for such iatrogenic effects is mixed (e.g., Huefner, Handwerk, Ringle, & Field, 2009; Weiss et al, 2005), however, which suggests that such effects may be complex.…”
Section: Discussionmentioning
confidence: 99%
“…However, in their study, the majority of youth did not show an increase in problem behavior during treatment. Also, several other studies found that exposure to deviant peers during residential treatment was not related to increase in conduct behaviors (Huefner et al, 2009;Huefner & Ringle, 2012). A recent study by Huefner et al (2018) in which both positive and negative peer influences in residential care were examined showed that positive peer influences were associated with lower rates of serious problem behavior.…”
Section: Peer Interactions In Residential Youth Carementioning
confidence: 92%
“…Studies on peer interactions among troubled youth often focus on negative influences that youth might have on each other. For example, there has been an ongoing debate about the extent to which youth in residential care learn criminal behavior from others during their stay, often referred to as peer contagion or deviancy training (Anderson, 1999;Bayer et al, 2009;Chein et al, 2011;Dishion et al, 1999;Dishion & Tipsord, 2011;Huefner et al, 2009;Weiss et al, 2005;Welsh & Rocque, 2014). Parhar et al (2008) even argue that deviancy training in secure residential care hampers positive treatment outcomes so badly that placement is best to be avoided altogether.…”
Section: Peer Interactions In Residential Youth Carementioning
confidence: 99%